Surface immobilization of bio-functionalized cubosomes sensing of proteins by quartz crystal microbalance - Fraser, Scott J (Langmuir : the ACS journal of surfaces and colloids, 2012)
A strategy for tethering lipid liquid crystalline submicrometer particles (cubosomes) to a gold surface for the detection of proteins is reported. Time-resolved quartz crystal microbalance (QCM-D) was used to monitor the cubosome-protein interaction in real time. To achieve specific binding, cubosomes were prepared from the nonionic surfactant phytantriol, block-copolymer, Pluronic F-127, and a secondary biotinylated lipid, 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[biotinyl(polyethyleneglycol)-2000], which enabled attachment of the particles to a neutravidin (NAv)-alkanethiol monolayer at the gold surface of the QCM sensor chip. A second set of cubosomes was further functionalized with addition of the glycolipid (G(M1)) to facilitate a specific binding uptake of the protein, cholera toxin B subunit (CT(B)), from solution. QCM-D confirmed the specificity of the cubosome-NAv binding. The analysis of titration experiments, also performed with QCM, suggests that an optimal concentration of cubosomes is required for the efficient packing of the particles at the surface: high cubosome concentrations lead to chaotic cubosome binding onto the surface, sterically inhibiting surface attachment, or require significant reorganization to permit uniform cubosome coverage. The methodology enabled the straightforward preparation of a complex nanostructured edifice, which was then used to specifically capture analyte proteins (cholera toxin B subunit or free NAv) from solution, supporting the potential for development of this approach as a biosensing platform